Kinetics studies of p-cresol biodegradation by using Pseudomonas putida in batch reactor and in continuous bioreactor packed with calcium alginate beads - Mathur, A K (Water science and technology : a journal of the International Association on Water Pollution Research, 2010)
Present study deals with the biodegradation of p-cresol by using Pseudomonas putida in a batch reactor and a continuous bioreactor packed with calcium alginate beads. The maximum specific growth rate of 0.8121 h(-1) was obtained at 200 mg L(-1) concentration of p-cresol in batch reactor. The maximum p-cresol degradation rate was obtained 6.598 mg L(-1) h(-1) at S(o)=200 mg L(-1) and 62.8 mg L(-1) h(-1) at S(o)=500 mg L(-1) for batch reactor and a continuous bioreactor, respectively. The p-cresol degradation rate of continuous bioreactor was 9 to 10-fold higher than those of the batch reactor. It shows that the continuous bioreactor could tolerate a higher concentration of p-cresol. A Haldane model was also used for p-cresol inhibition in batch reactor and a modified equation similar to Haldane model for continuous bioreactor. The Haldane parameters were obtained as µ(max) 0.3398 h(-1), K(s) 110.9574 mg L(-1), and K(I) 497.6169 mg L(-1) in batch reactor. The parameters used in continuous bioreactor were obtained as D(max) 91.801 mg L(-1) h(-1), K(s) 131.292 mg L(-1), and K(I) 1217.7 mg L(-1). The value K(I) of continuous bioreactor is approximately 2.5 times higher than the batch reactor. Higher K(I) value of continuous bioreactor indicates P. putida can grow at high range of p-cresol concentration. The ability of tolerance of higher p-cresol concentrations may be one reason for biofilm attachment on the packed bed in the continuous operation